Modification of Jet Structure in High-Multiplicity pp Collisions due to Multiple-Parton Interactions and Observing a Multiplicity-Independent Characteristic Jet Size - Zoltán Varga; Róbert Vértesi; Gergely Gábor Barnaföldi (Advances in High Energy Physics)
We study the multiplicity dependence of jet structures in pp collisions using Monte Carlo event generators. We give predictions for multiplicity-differential jet structures and present evidence for a nontrivial jet shape dependence on charged hadron event multiplicity that can be used as a sensitive tool to experimentally differentiate between equally well-preforming simulation tunes. We also propose a way to validate the presence and extent of effects such as multiple-parton interactions (MPI) or color reconnection (CR), based on the detection of nontrivial jet shape modification in high-multiplicity events at high pT. Using multiplicity-dependent jet structure observables in various pT windows might also help understanding the interplay between jet particles and the underlying event (UE). We introduce a multiplicity-independent characteristic jet size measure and use a simplistic model to aid its physical interpretation.